?NEGATIVE PURIFICATION OF THE PLASMA MEMBRANE ATPASE OF RHODOTORULA GLUTINIS (Biological Sciences - PJSIR, 1999)
The ATPase from the aerobic yeast Rhodotorula glutinis was purified by removing undesirable proteins. Four different reagents proved effective in removing about 50% of undesirable proteins (peripheral membrane and/or cytoplasmic pro- teins that might be trapped during membrane isolation). The plasma membrane suspensions were treated with KCI (2M), followed by lysophosphatidylcholine (0.001 %, wv .1), then Triton (0.02%, wv .1) and finally deoxycholate (4 mM). This resulted in removal of 50 % of the proteins while increasing the ATP ase activity 20% above the control level, resulting in about 2.5-fold purification.